Consideration of Insulin Pumps or Continuous Glucose Monitors by Adolescents With Type 1 Diabetes and Their Parents: Stakeholder Engagement in the Design of Web-Based Decision Aids. (August 2016) - Wysocki, Tim; Hirschfeld, Fiona; Miller, Louis; Izenberg, Neil; Dowshen, Steven A.; Taylor, Alex; Milkes, Amy; Shinseki, Michelle T.; Bejarano, Carolina; Kozikowski, Chelsea; Kowal, Karen; Starr-Ashton, Penny; et al.
Purpose: This article describes the stakeholder-driven design, development, and testing of web-based, multimedia decision aids for youth with type 1 diabetes who are considering the insulin pump or continuous glucose monitoring and their parents. This is the initial phase of work designed to develop and evaluate the efficacy of these decision aids in promoting improved decision-making engagement with use of a selected device. Methods: Qualitative interviews of 36 parents and adolescents who had previously faced these decisions and 12 health care providers defined the content, format and structure of the decision aids. Experts in children's health media helped the research team to plan, create, and refine multimedia content and its presentation. A web development firm helped organize the content into a user-friendly interface and enabled tracking of decision aid utilization. Throughout, members of the research team, adolescents, parents, and 3 expert consultants offered perspectives about the website content, structure, and function until the design was complete. Results: With the decision aid websites completed, the next phase of the project is a randomized controlled trial of usual clinical practice alone or augmented by use of the decision aid websites. Conclusions: Stakeholder-driven development of multimedia, web-based decision aids requires meticulous attention to detail but can yield exceptional resources for adolescents and parents contemplating major changes to their diabetes regimens.